PERANCANGAN ASSESMEN LITERASI KIMIA DENGAN MENGGUNAKAN MODEL OF EDUCATIONAL REKONSTRUCTION (MER) PADA TEMA: âAIR SEBAGAI PELARUT UNIVERSALâ - Yusmaita, Eka; Nasra, Edi (JURNAL EKSAKTA PENDIDIKAN (JEP), 2017)
This research aims to produce instrument for measuring chemical literacy assessment in basic chemistry courses with theme âwater as a universal solventâ. The construction of this measuring instrument is adapted to the PISA (Programme for International Student Assessment) problemâs characteristics and the Syllaby of Basic Chemistry in KKNI-Indonesian National Qualification Framework. The PISA is a cross-country study conducted periodically to monitor the outcomes of learners achievement in each participating country. So far, studies conducted by PISA include reading literacy, mathematic literacy and scientific literacy. Refered to the scientific competence of the PISA study on science literacy, an assessment designed to measure the chemical literacy of the chemistry departmentâs students in UNP. The research model used is MER (Model of Educational Reconstruction). The validity and reliability values of discourse questions is measured using the software ANATES. Based on the acquisition of these values is obtained a valid and reliable chemical literacy questions. There are four question items limited response on the theme with valid category, the acquisition value of test reliability is 0,60 and has a difficulty index and distinguishing good